Optical, Spectroscopic, and Doppler Evaluation of “Normal” and “Abnormal” Reflexology Areas in Lumbar Vertebral Pathology: A Case Study - Krishna Dalal; D. Elanchezhiyan; V. B. Maran; Raunak Kumar Das; Piyush Kumar; S. P. Singh; C. Murali Krishna; Jyotirmoy Chatterjee (Case Reports in Medicine)
Scientific validation of reflexology requires an in-depth and noninvasive evaluation of “reflexology/reflex areas” in health and disease. The present paper reports the differential properties of “normal” and “abnormal” reflexology areas related to the lumbar vertebrae in a subject suffering from low back pain. The pathology is supported by radiological evidence. The reflexology target regions were clinically assessed with respect to colour and tenderness in response to finger pressure. Grey scale luminosity and pain intensity, as assessed by visual analogue scale scores, differentiated “normal” from “abnormal” skin. Skin swept source-optical coherence tomography recorded their structural differences. Infrared thermography revealed temperature variations. A laser Doppler study using a combined microcirculation and transcutaneous oxygen monitoring system indicated alterations in blood flow and oxygen perfusion. Raman spectroscopy showed differences in chemical signatures between these areas. The present findings may indicate a potential correlation between the reflexology areas and subsurface pathological changes, showing an association with the healthy or unhealthy status of the lumbar vertebrae.